2011
DOI: 10.2215/cjn.06240710
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care-Specialist Collaboration in the Care of Patients with Chronic Kidney Disease

Abstract: SummaryBackground and objectives Collaboration between primary care physicians (PCPs) and nephrologists in the care of patients with chronic kidney disease (CKD) is widely advocated, but physician preferences regarding collaboration are unknown. Physicians' desires to collaborate in the care of a hypothetical patient with CKD, their preferred content of collaboration, and their perceived barriers to collaboration were assessed.Design, setting, participants, & measurements A questionnaire describing the care of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 24 publications
0
38
0
1
Order By: Relevance
“…These observations may reflect patterns of nephrologist referral by primary care physicians that may vary depending on their self-efficacy in managing CKD, interaction with nephrologists, and perceived patient barriers to health care access. 1820 Nephrologist care is strongly recommended for all patients with CKD stages 4–5 because early nephrology referral is associated with reduced morbidity and mortality when dialysis therapy is started, 21 but not all patients with CKD stage 3 need to be seen by a nephrologist, especially those without proteinuria or at low risk of progression (eg, eGFR consistently >45 mL/min/1.73 m 2 ). 22 In our cohort, rates of nephrology visits were lower than reported elsewhere, 23 which may be explained in part by study design.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may reflect patterns of nephrologist referral by primary care physicians that may vary depending on their self-efficacy in managing CKD, interaction with nephrologists, and perceived patient barriers to health care access. 1820 Nephrologist care is strongly recommended for all patients with CKD stages 4–5 because early nephrology referral is associated with reduced morbidity and mortality when dialysis therapy is started, 21 but not all patients with CKD stage 3 need to be seen by a nephrologist, especially those without proteinuria or at low risk of progression (eg, eGFR consistently >45 mL/min/1.73 m 2 ). 22 In our cohort, rates of nephrology visits were lower than reported elsewhere, 23 which may be explained in part by study design.…”
Section: Discussionmentioning
confidence: 99%
“…This helps translate research results to clinical care, lowering well known barriers to the implementation of existing practice guidelines for care of patients with CKD. 27,28 The majority of CKD patients are cared for by primary care providers with or without collaboration with nephrologists, 8,29 and PCTs may be well positioned to affect CKD care in the primary care setting. Examples of studies bridging nephrology and primary care include trials of CKD care coordination with patient navigators 30 and strategies to implement guidelineconcordant CKD care with electronic checklists, 31 primary care practice facilitation, 32 and pharmacist-led interventions.…”
Section: Potential Benefits Of Pct Designs In Ckdmentioning
confidence: 99%
“…26 A subsequent study showed that primary care physicians with more than 10 years in practice were least likely to recommend referral of patients with CKD but more likely to express a desire for collaborative care, yet the differences were small (89% vs 82%). 27,28 General internists who were aware of existing guidelines were 14 times more likely to recommend referral. 27 …”
Section: Discussionmentioning
confidence: 99%